Avaliação da ação dos aditivos orgânicos na interface metal/solução no processo de eletrodeposição de níquel - SCHMITZ, EDINÉIA PAULA SARTORI (2016)
This study aimed at evaluating the organic additive action mechanism in nucleation and growth of nickel layers, employing a commercial organic additive class, with good anti corrosion performance, widely used in the country industry. The class under study is composed of a carrier additive, a brightener additive and a wetting agent; such names employed in the industry were defined by the product manufacturer. These additives action was studied in two phases, the first through a 25-1 factorial experimental design and principal component analysis, and the second through the analysis of chronoamperometric transients and the application of nucleation and growth theory. The variables of the experimental design were presence and absence of the three additives, load and density of the current applied in a Hull cell system. The responses evaluated were roughness, resistance to load transfer and the brightness of the layers obtained. The factorial design was seen as a satisfactory tool to evaluate the additives synergic and antagonistic effects. The presence of additives alters significantly the sample brightness. The wetting agent affects this property in the deposited layer. The study of superficial morphologies allowed the identification of three great morphological groups in the deposited films, which are: needle, flat pyramid and apparently smooth film shapes in the scale observed (atomic force microscopy). The tests carried out with common morphological structure samples appear grouped in the principal component analysis, showing strong dependence between morphology and the responses under study: brightness, roughness and resistance to load transfer. The two main components in the principal component analysis captured, respectively, 60.51% and 26.25% of the experimental variance. Roughness was negatively correlated to brightness (expected effect) through the component 1 and the polarization resistance was negatively correlated with brightness through the component 2. In general, the class of additives under study was observed to present optimized industrial formulation for brightness maximization, which implies, according to the principal component analysis results, resistance to the non-optimized load transfer. The second phase of the study was the evaluation of additive action in the film nucleation and growth. The electrodes polishing and cleaning processes were shown a determining factor to obtain good results for the nucleation analysis, and the preparation was optimized throughout the research. The glassy carbon was not shown reproducible for tests, nor the carbon steel electrode for the nucleation study, therefore, a platinum electrode was employed. It was possible to identify the nickel nuclei formed, and these were nanometrically-sized (between 60 and 150nm). Nickel growth both in the presence and absence of additives was identified as tridimensional and with instantaneous nucleation. The presence of brightener and carrier increased significantly the velocity of bidimensional growth of the previously formed monolayers. No significant effects were identified on the kinetics of the nickel growth, neither for wetting and brightener agents alone nor in combination with each other, only for the combination between brightener and carrier.